Electronic word of mouth, purchase intention, and loyalty in West Java broadband with happiness as a moderator - Ramdan, Asep Muhamad; Nurmala, Resa; Komariah, Kokom; Jhoansyah, Dicky (Goodwood Publishing, 2025)
Purpose: This study aims to examine how electronic word of mouth (eWOM) specifically information quality, quantity, and credibility influences purchase intention and customer loyalty among IndiHome subscribers in West Java. Additionally, it tests whether happiness moderates the relationship between purchase intention and loyalty. Methodology: The research employed a quantitative, cross-sectional design using stratified random sampling of 257 IndiHome subscribers across multiple municipalities in West Java. Data were collected through structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate measurement validity, reliability, mediation, and moderation effects. Results/findings: Findings show that information quality and quantity significantly increase purchase intention, while credibility has no direct effect. Purchase intention strongly predicts loyalty. Quantity and credibility indirectly affect loyalty through intention, whereas quality does not. Happiness moderates intention–loyalty, strengthening the conversion of intention into sustained customer loyalty. Conclusion: The study concludes that clear and abundant eWOM cues are effective in shaping purchase intention, which serves as a key determinant of loyalty. Positive affect in the form of happiness amplifies this relationship, highlighting the importance of both cognitive and emotional drivers in loyalty formation. Limitations: The cross-sectional design limits causal inference, and reliance on self-reported measures may introduce bias. The provincial focus on West Java may also restrict generalizability. Contribution: This research extends eWOM theory by integrating informational attributes with affective moderation, offering both theoretical insights and managerial implications. Broadband providers are advised to improve information clarity, posting frequency, and service experiences that enhance customer happiness to foster sustainable loyalty.